Keterlibatan Warga Negara Muda dalam Gerakan Kewarganegaraan Ekologis untuk Mewujudkan Pembangunan Berkelanjutan Berwawasan Lingkungan - Leha Silfiana; Samsuri Samsuri (Universitas Gadjah Mada, 2019)
Young citizens have a strategic role in the movement to care for the environment. They are considered as guardian angels for the environment from the cruel economic development and development. Their involvement in the environmental movement will have a major impact on environmental sustainability. The ecological citizenship movement can be a bridge to bring young citizens to the success of environmentally sustainable development. The ecological citizenship movement is a social activity that focuses its activities on saving the environment from human selfish actions. The purpose of this study is to analyze the importance of the involvement of young citizens in the ecological citizenship movement to realize sustainable development with an environmental perspective. This research uses a literature study approach. Data sources were obtained from the results of reviews of journal articles or books related to ecological citizenship, sustainable development, and case studies on the involvement of young citizens in environmental management. This article consists of three discussions that fit the focus of this research. First, it outlines a description of the ecological citizenship movement. Second, it presents the results of an analysis of the forms of involvement of young citizens in the ecological citizenship movement from various case studies. Third, present the results of an analysis of the importance of the involvement of young citizens in environmentally sustainable development. Based on the results of the study it can be concluded that the involvement of young citizens in the ecological citizenship movement and sustainable development programs is very important, because they are the actors responsible for environmental sustainability and development in the future.